Cognitive processing speed is related to fall frequency in older adults with multiple sclerosis - Sosnoff, Jacob J; Balantrapu, Swathi; Pilutti, Lara A; Sandroff, Brian M; Morrison, Steven; Motl, Robert W (Archives of physical medicine and rehabilitation, 2013)
To examine mobility, balance, fall risk, and cognition in older adults with multiple sclerosis (MS) as a function of fall frequency. Retrospective, cross-sectional design. University research laboratory. Community-dwelling persons with MS (N=27) aged between 50 and 75 years were divided into 2 groups-single-time (n=11) and recurrent (n=16; >2 falls/12 mo) fallers-on the basis of fall history. Not applicable. Mobility was assessed using a variety of measures including Multiple Sclerosis Walking Scale-12, walking speed (Timed 25-Foot Walk test), endurance (6-Minute Walk test), and functional mobility (Timed Up and Go test). Balance was assessed with the Berg Balance Scale, posturography, and self-reported balance confidence. Fall risk was assessed with the Physiological Profile Assessment. Cognitive processing speed was quantified with the Symbol Digit Modalities Test and the Paced Auditory Serial Addition Test. Recurrent fallers had slower cognitive processing speed than single-time fallers (P ≤.01). There was no difference in mobility, balance, or fall risk between recurrent and single-time fallers (P>.05). Results indicated that cognitive processing speed is associated with fall frequency and may have implications for fall prevention strategies targeting recurrent fallers with MS.